Purpose-movement assisted routing for group mobility in disconnected mobile ad hoc networks - Xie, Ling Fu (2013)
As a challenged network, the delay-tolerant network (DTN) generally has unpredictable delay for the packet delivery due to the insufficiency of the network connectivity. Thus, it is inadequate to support some time-sensitive applications. In this paper we aim to mitigate this unpredictability of the delay in DTN to broaden its applications by proposing a new routing strategy to make use of the node mobility. Our designed solution is called purpose-movement assisted routing (PMAR) aiming for a more realistic mobility model, group mobility, which has been paid attention in many realistic scenarios. Different from the traditional store-carry-forward DTN routing strategy, in which nodes wait for the connectivity passively, PMAR employs nodes to actively create new connection by altering the node movement, and thus the packet could be delivered in an expedited manner. More importantly, the proposed PMAR could be taken as a component to be integrated into different DTN routings for group mobility to make them more aggressive in delivering packets. In this paper, we integrate PMAR into a previously proposed routing, group-epidemic routing (G-ER). PMAR could be triggered whenever some packets need to be delivered to the destinations in a faster way, but without any connection to their destinations. By computer simulation, it is found that PMAR could greatly improve G-ER, especially the packet delay.